2009
DOI: 10.1002/hep.23289
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for increased expression of cholesterol 7α-hydroxylase (Cyp7a1) in lactating rats

Abstract: Cholesterol 7␣-hydroxylase (Cyp7a1) and the bile acid pool size are increased 2 to 3-fold in lactating postpartum rats. We investigated the interaction of nuclear receptors with the Cyp7a1 proximal promoter and the expression of regulatory signaling pathways in postpartum rats at day 10 (PPd10) versus female controls to identify the mechanisms of increased expression of Cyp7a1, which is maximal at 16 hours. Liver X receptor (LXR␣) and RNA polymerase II (RNA Pol II) recruitment to Cyp7a1 chromatin were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…To our knowledge, the expression of LXRα and its genes involved in bile acid synthesis and cholesterol export in dairy cows during lactation has not yet been investigated in other studies. The results of this study, however, are well in agreement with studies in rats, which also found an increased expression or activity of CYP7A1 in the liver during lactation (Smith et al, 1998;Wooton-Kee et al, 2010;Athippozhy et al, 2011). The upregulation of CYP7A1 has been attributed to an increased recruitment of LXRα, which is in agreement with the present findings, and to a decreased expression of FGF15 and phosphorylated Erk1/2, which are acting as CYP7A1 repressive pathways (Wooton-Kee et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, the expression of LXRα and its genes involved in bile acid synthesis and cholesterol export in dairy cows during lactation has not yet been investigated in other studies. The results of this study, however, are well in agreement with studies in rats, which also found an increased expression or activity of CYP7A1 in the liver during lactation (Smith et al, 1998;Wooton-Kee et al, 2010;Athippozhy et al, 2011). The upregulation of CYP7A1 has been attributed to an increased recruitment of LXRα, which is in agreement with the present findings, and to a decreased expression of FGF15 and phosphorylated Erk1/2, which are acting as CYP7A1 repressive pathways (Wooton-Kee et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…as mitogen-activated protein kinase (maPK) has also been shown to regulate Cyp7a1 transcription (22)(23)(24), the phosphorylation of p38, erK and jnK was examined in livers treated with proteasome inhibitors. Hepatic phosphorylation of jnK and erK, but not p38, was elevated upon administration of Bt and cf ( fig.…”
Section: Genesmentioning
confidence: 99%
“…FXR has been reported to play a critical role in bile acid homeostasis (7)(8)(9). FXR activation transiently induces the expression of small heterodimer partner (Shp) and fibroblast growth factor 15 (Fgf15) in mice, and elevated levels of Shp and Fgf15 in turn lead to transcriptional repression of genes involved in bile acid synthesis (10,11). In addition, FXR can down-regulate Na + /taurocholate cotransporting polypeptide (Ntcp), which prevents bile acids uptake into hepatocytes, and induce expression of bile salt export pump (Bsep), which increases bile acid efflux from the liver into bile.…”
Section: Introductionmentioning
confidence: 99%